2018
DOI: 10.1016/j.watres.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Portable platform for rapid in-field identification of human fecal pollution in water

Abstract: Human fecal contamination of water is a public health risk. However, inadequate testing solutions frustrate timely, actionable monitoring. Bacterial culture-based methods are simple but typically cannot distinguish fecal host source. PCR assays can identify host sources but require expertise and infrastructure. To bridge this gap we have developed a field-ready nucleic acid diagnostic platform and rapid sample preparation methods that enable on-site identification of human fecal contamination within 80 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 56 publications
0
62
0
Order By: Relevance
“…We have previously demonstrated that the ready-to-use LAMP-OSD assay mixes can be lyophilized and stored for extended durations without loss of activity. 13 These various features should minimize device intricacies, and in turn reduce cost, especially since only two protein enzymes and a single fluorophore-quencher pair are required. Most importantly, the molecular probes can be configured to capture both current and future fast-evolving targets, such as the Zika viruses, with both greater breadth and greater accuracy than existing tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that the ready-to-use LAMP-OSD assay mixes can be lyophilized and stored for extended durations without loss of activity. 13 These various features should minimize device intricacies, and in turn reduce cost, especially since only two protein enzymes and a single fluorophore-quencher pair are required. Most importantly, the molecular probes can be configured to capture both current and future fast-evolving targets, such as the Zika viruses, with both greater breadth and greater accuracy than existing tests.…”
Section: Discussionmentioning
confidence: 99%
“…Following 90 -120 min of amplification at 65 °C, the reactions were imaged at room temperature using an unmodified iPhone 6 and an UltraSlim-LED transilluminator (Syngene, Frederick, MD, USA). In some experiments, our previously described in-house 3D-printed imaging device 13 was used for fluorescence visualization and smartphone imaging. Briefly, this device uses Super Bright Blue 5 mm light emitting diodes (LED) (Adafruit, New York, NY, USA) to excite fluorescence.…”
Section: One-pot Rt-lamp Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these barriers to the use of LAMP, we have previously adopted methods that originated in the field of nucleic acid computation: the use of strand exchange reactions that initiate at complementary single-stranded ‘toeholds’ and progresses via branch migration. The base-pairing predictability and programmability of strand exchange kinetics promotes the construction of exquisitely sequence-specific oligonucleotide strand displacement (OSD) probes for LAMP amplicons ( S2 Fig ), thereby greatly reducing the detection of non-specific amplification background [39, 41, 42]. For instance, we recorded positive coi LAMP-OSD signals from field-caught Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since our assays can accurately analyze mosquitoes several days after capture – the coi LAMP-OSD assay could for example identify mosquitoes after 3 weeks at 37 °C without desiccant – mosquitoes from remote collection outposts can potentially be analyzed even after delayed retrieval. The flexibility of assay timing is further accommodated by the fact that lyophilized LAMP-OSD reaction mixes that can be stored and deployed without cold chain [42]. These combined features make our assay platform the best tool to date for expanding vector surveillance to resource poor settings [72], especially in that the ease of use should allow minimally trained citizen scientists to participate in otherwise sophisticated public health monitoring operations in the field.…”
Section: Discussionmentioning
confidence: 99%